PERMASALAHAN PELAYANAN PUBLIK DAN PERAN OMBUDSMAN PERWAKILAN DALAM PENDAMPINGAN APARATUR SIPIL NEGARA - Andi Setyo Pambudi (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2023)
Public services in practice are always related to service delivery institutions and the community as service recipients. One institution that provides public services is the State Civil Apparatus (ASN). The Indonesian Ombudsman, a public service supervisory agency mandated by Indonesia's regulations in Indonesia, assists the apparatus in the form of efforts to prevent maladministration. However, this institution in the regions (representatives) is better known for resolving community reports/complaints in public services. Meanwhile, public service development planning must pay attention to these two aspects (solution and prevention) in a more balanced manner based on existing problems, institutional supervisory agencies, their authorities, and their level of popularity in the region. The analysis results indicate several crucial issues that need to be addressed based on priority, urgency, location, and public opinion. The role and popularity of the Ombudsman, both at the central and regional levels, in assisting state civil servants in carrying out public services and the problems are interesting to be studied more comprehensively. Many good practices, their roles, and problems in the field can be used as input to develop public services as part of the support for national priorities in the National Mid-Term Development Plan. The method used in this analysis is a mixed-method through literature review, Big Data analysis, and Focus Group Discussion (FGD). The analysis results show that, in general, the Ombudsman has carried out his role in assisting, which can still be improved with the support of budgets, regulations, facilities, infrastructure, and human resources